TUJUAN, FUNGSI, SASARAN DAN MANFAAT SUPERVISI AKADEMIK - Fatkhan Munif (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
Supervision is a service from superiors to subordinates by givingdirection to improve performance for the be